Pengaruh Dana Desa Terhadap Pendapatan Masyarakat Desa Apren Kecamatan Amarasi Kabupaten Kupang Tahun 2022-2024 - Eknoe, Arwilda; Made Susilawati; Cernan,Chr, A, Liu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This thesis, written by Arwilda Eknoe (National Student ID: 2162201007), is titled "The Effect of Village Fund Management on Community Income in Apren Village, Amarasi District, Kupang Regency, 2022-2024." This study aims to determine the effect of Village Fund management on community income in Apren Village, Amarasi District, Kupang Regency. The method used in this study is quantitative with a descriptive approach. The data used are primary data from interviews and direct observations, as well as secondary data in the form of Village Fund realization reports and community income data. The analysis used was simple linear regression, t-test, and coefficient of determination (R²) using SPSS. The results show that Village Funds have a positive and significant effect on increasing community income. This is evidenced by the statistical analysis, which shows a significance value of less than 0.05. Furthermore, the community acknowledged that programs funded by Village Funds, such as infrastructure development and economic empowerment, have had a direct impact on increasing their income.